A thermoelectric power generating heat exchanger: Part I – Experimental realization. (1st July 2016) - Bjørk, R.; Sarhadi, A.; Pryds, N.; Lindeburg, N.; Viereck, P.
Highlights: A power generating thermoelectric heat exchanger is presented. The device can produce 2 W per TEG at a hot fluid temperature of 175 °C. A device producing 200 W from 100 TEGs is demonstrated. Temperature span across the TEGs are 55–75% of the fluid temperature span. Abstract: An experimental realization of a heat exchanger with commercial thermoelectric generators (TEGs) is presented. The power producing capabilities as a function of flow rate and temperature span are characterized for two different commercial heat transfer fluids and for three different thermal interface materials. The device is shown to produce 2 W per TEG or 0.22 W cm −2 at a fluid temperature difference of 175 °C and a flow rate per fluid channel of 5 L min −1 . One experimentally realized design produced 200 W in total from 100 TEGs. For the design considered here, the power production is shown to depend more critically on the fluid temperature span than on the fluid flow rate. Finally, the temperature span across the TEG is shown to be 55–75% of the temperature span between the hot and cold fluids.